Capacitación científica y actividades de las redes - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
Scientific training at CIAT continues to support the efforts of researchers particularly with respect to the training of technicians in the evaluation of promising germplasm. For training outside CIAT headquarters, greater emphasis was given to the study of limiting bean production factors at the national and local levels. Lists of in-country curses, professionals and visiting researchers trained at CIAT, as well as major achievements in 1984, are presented. A summary of the network research activities in beans in Central America, the Caribbean, Brazil, Peru, and Eastern Africa is presented. The information provided includes adaptation nurseries, on-farm research, feedback of information to CIAT, and transfer of technology from CIAT to national programs. Regarding the Great Lakes Regional Bean Program, the region is described and project activities, var. development, research on nutrition and quality, and future plans are summarized. (CIAT)